KAJIAN BIOAKTIF DAN ZAT GIZI PROPOLIS INDONESIA DAN BRASIL - Eliza Halim; Hardinsyah Hardinsyah; Noorwati Sutandyo; Ahmad Sulaeman; Made Artika; Yahdiana Harahap (Food and Nutrition Society of Indonesia, 2012)
Indonesia has a potency to produce its own propolis, however the propolis market in Indonesia is dominated by imported product, such as from Brazil. Currently, still there is no reasearch which evaluate bioactive compound and nutrient content of Indonesian Propolis (IP) compare with Brazilian Propolis (BP). The objectives of this study were to analyze bioactive compounds and nutrient contents of IP compared to BP. Bioactive compounds and nutrients content were analyzed by gas chromatography–mass spectrophotometry. The resultsshowed both IP and BP contain fenol, α-amyrin, cylolanost, and pyrimidines. Bioactive compounds which specifically found in IP were eudesmane compound, ethyl acridine, lupeol, friedooleanan; while β amyrin and cinnamic acid compound only found in BP. The nutrient contents of IP were higher than BP except for vitamin A. In conclusion, IP might have potential health benefit, similar to BP.